The heritage of Arabo-Islamic learning studies presented to Wadad Kadi - Qāḍī, Wadād; Pomerantz, Maurice A.; Shahin, Aram A. (Islamic history and civilization : studies and texts, 2016)
The Arabo-Islamic heritage of the Islam is among the richest, most diverse, and longest-lasting literary traditions in the world. Born from a culture and religion that valued teaching, Arabo-Islamic learning spread from the seventh century and has had a lasting impact until the present.In The Heritage of Arabo-Islamic Learning leading scholars around the world present twenty-five studies explore diverse areas of Arabo-Islamic heritage in honor of a renowned scholar and teacher, Dr. Wadad A. Kadi (Prof. Emerita, University of Chicago). The volume includes contributions in three main areas: History, Institutions, and the Use of Documentary Sources; Religion, Law, and Islamic Thought; Language, Literature, and Heritage which reflect Prof. Kadi's contributions to the field.